Pengaruh Komposisi Campuran Limbah Filter Rokok dan Serbuk Kayu Terhadap Kemampuan Redam Material Komposit - Mulawarman, Mulawarman; Udayana, I Nyoman; Samhuddin, Samhuddin; Aksar, Prinob; Aminur, Aminur (Teknik Mesin Universitas Halu Oleo, 2024)
Waste is a residual production material that contains substances capable of causing pollution and health disturbances. One of the waste types frequently encountered is cigarette filter waste and wood powder waste, both of which are managed minimally. This research aims to determine the influence of the composition of a mixture of cigarette filter waste and wood powder waste on sound absorption in composite materials. The method involved preparing the necessary tools and materials, then creating composites with fractions (65%, 20%: 10%, 15%), (60%, 20%: 13%, 7%), and (55%, 20%: 15%, 10%). Subsequently, sound absorption testing was conducted using the direct method following ISO 11654 standards. Results from the sound absorption testing at a frequency of 500 Hz showed the highest sound intensity value in the fraction (65%, 20%: 10%, 15%) at 104,833 dBa and the lowest in the fraction (55%, 20%: 15%, 10%) at 93,333 dBa. The highest sound absorption coefficient value was found in the fraction (55%, 20%: 15%, 10%) at 0,202, while the lowest was in the fraction (65%, 20%: 10%, 15%) at 0,104. As the volume of acoustic material from cigarette filter waste and wood powder waste increased, the sound absorption coefficient also increased. The best sound absorption coefficient value was observed in the fraction (55%, 20%: 15%, 10%) at 0,202